Analisis Perbandingan Metode Foss Nirs dan Metode Ekstraksi dalam Optimasi Pengendalian Oil Losses pada Drab Akhir di Pabrik Kelapa Sawit Line 1 Kapasitas 30 TPH (Studi Kasus: PTPN IV Regional 1 PKS Sei Mangkei) - Alfina, Febi Silvia; Fuadi, M Hifzhil (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The palm oil industry requires efficient production systems to minimize oil losses and maintain product quality. One critical point of oil loss occurs in final drab from the clarification process, which still contains residual oil. This study aims to analyze and compare oil losses in final drab using the extraction (Soxhlet) method and the FOSS Near Infrared Reflectance Spectroscopy (NIRS) method. The research was conducted at PT Perkebunan Nusantara IV Regional I PKS Sei Mangkei using final drab samples collected from 28 July to 2 August 2025. The results show that oil losses measured by the extraction method ranged from 0.27% to 0.63%, while the FOSS NIRS method ranged from 0.07% to 0.36%. Most values were within the company standard of 0.50%. NIRS is recommended for routine monitoring due to faster analysis, while periodic calibration with the extraction method is required to maintain accuracy.